Organizational readiness for knowledge translation in chronic care: a review of theoretical components - Attieh, Randa; Gagnon, Marie-Pierre; Estabrooks, Carole A; Légaré, France; Ouimet, Mathieu; Roch, Geneviève; Ghandour, El K; Grimshaw, Jeremy (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background With the persistent gaps between research and practice in healthcare systems, knowledge translation (KT) has gained significance and importance. Also, in most industrialized countries, there is an increasing emphasis on managing chronic health conditions with the best available evidence. Yet, organizations aiming to improve chronic care (CC) require an adequate level of organizational readiness (OR) for KT. Objectives: The purpose of this study is to review and synthesize the existing evidence on conceptual models/frameworks of Organizational Readiness for Change (ORC) in healthcare as the basis for the development of a comprehensive framework of OR for KT in the context of CC. Data sources We conducted a systematic review of the literature on OR for KT in CC using Pubmed, Embase, CINAHL, PsychINFO, Web of Sciences (SCI and SSCI), and others. Search terms included readiness; commitment and change; preparedness; willing to change; organization and administration; and health and social services. Study selection: The search was limited to studies that had been published between the starting date of each bibliographic database (e.g., 1964 for PubMed) and November 1, 2012. Only papers that refer to a theory, a theoretical component from any framework or model on OR that were applicable to the healthcare domain were considered. We analyzed data using conceptual mapping. Data extraction: Pairs of authors independently screened the published literature by reviewing their titles and abstracts. Then, the two same reviewers appraised the full text of each study independently. Results Overall, we found and synthesized 10 theories, theoretical models and conceptual frameworks relevant to ORC in healthcare described in 38 publications. We identified five core concepts, namely organizational dynamics, change process, innovation readiness, institutional readiness, and personal readiness. We extracted 17 dimensions and 59 sub-dimensions related to these 5 concepts. Conclusion Our findings provide a useful overview for researchers interested in ORC and aims to create a consensus on the core theoretical components of ORC in general and of OR for KT in CC in particular. However, more work is needed to define and validate the core elements of a framework that could help to assess OR for KT in CC.